2014
DOI: 10.7567/jjap.53.091102
|View full text |Cite
|
Sign up to set email alerts
|

Single crystalline In–Ga–Zn oxide films grown from c-axis aligned crystalline materials and their transistor characteristics

Abstract: In this study, we analyzed the crystallinity of c-axis aligned crystalline In–Ga–Zn oxide (CAAC-IGZO) and single crystalline (sc) IGZO films. CAAC-IGZO films were formed on (111)-oriented yttria-stabilized-zirconia substrates by magnetron sputtering using a target. Sc-IGZO films were obtained by annealing CAAC-IGZO films at 1200 °C. The proportion of Zn in the composition changed during growth of the films, and as a result, sc-InGaO3(ZnO)3 films w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 30 publications
(41 reference statements)
1
28
0
Order By: Relevance
“…Dr. Noboru Kimizuka, who first synthesized single‐crystalline IGZO, indicated that the crystal morphology of CAAC and nanocrystal (nc) should be classified as an intermediate state that is neither an amorphous structure nor a crystal structure. Similarly, Dr. Yoshio Waseda mentioned that CAAC and nc should be put in the category of a novel boundary region …”
Section: Caac‐igzomentioning
confidence: 99%
See 2 more Smart Citations
“…Dr. Noboru Kimizuka, who first synthesized single‐crystalline IGZO, indicated that the crystal morphology of CAAC and nanocrystal (nc) should be classified as an intermediate state that is neither an amorphous structure nor a crystal structure. Similarly, Dr. Yoshio Waseda mentioned that CAAC and nc should be put in the category of a novel boundary region …”
Section: Caac‐igzomentioning
confidence: 99%
“…18,19 CAAC-IGZO is a crystalline phase that has a structure in the boundary region between an amorphous structure and a crystal structure, including single crystal and polycrystal. [20][21][22][23][24][25] Dr. Noboru Kimizuka, who first synthesized single-crystalline IGZO, 1,2,26 indicated that the crystal morphology of CAAC 21 and nanocrystal (nc) [22][23][24] should be classified as an intermediate state that is neither an amorphous structure nor a crystal structure. Similarly, Dr. Yoshio Waseda mentioned that CAAC and nc should be put in the category of a novel boundary region.…”
Section: Caac-igzomentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, because of the durability of the CAAC-IGZO to etching gas, it is possible to adopt a channel-etch process [6]. Furthermore, the CAAC-IGZO can be formed on a glass substrate at a relatively low temperature, under 500 ºC, unlike the case of single crystal IGZO [7][8] requiring high temperature, 1200 ºC or higher. Now using these CAAC-IGZO FETs as a backplane, LCD panels have been mass produced [9].…”
Section: Figurementioning
confidence: 99%
“…Indium‐gallium‐zinc oxide (IGZO) can be given as one of the OS . The formation of a CAAC‐OS thin film over a glass substrate requires annealing at less than or equal to 500 °C . We succeeded in forming a channel‐etched OS field‐effect transistor (FET) that uses a CAAC‐IGZO for an active layer and has improved characteristics and improved reliability by lowering the defect levels …”
Section: Introductionmentioning
confidence: 99%